THE INFLUENCE OF PROFITABILITY, SOLVABILITY, ASSET GROWTH, AND SALES GROWTH TOWARD FIRM VALUE (Empirical Study on Mining Companies Which Listed on Indonesia Stock Exchange) - Vidyanita Hestinoviana (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This research was conducted to determine what factors may affect the firm value in the mining companies, because the company has a main objective to increase the firm value. Factors examined are internal factor. This research uses Profitability, Solvability, Asset Growth, and Sales Growth as independent variable and firm value as dependent variable. The results show that: Profitability, Solvability, Asset Growth, and Sales Growth simultaneously effect the firm value. Individually, Profitability and Sales Growth have no significant effect to Firm Value with regression coefficient (B) for Profitability is 0.19 and Sales Growth is 0.003, while Solvability and Asset Growth have significant effect to the Firm Value with B of Solvability is 0.463 and Asset Growth is -0.022. Keywords: Firm Value, Profitability, Solvability, Asset Growth, and Sales Growth